Religious Moderation as a Pillar of Character Education in the Digital Era - Ahmad Arinal Haq; Jamal Fahri; Rudy Irawan (IQRO: Journal of Islamic Education, 2026)
This study aims to analyze the urgency of religious moderation, focusing on tolerance as a pillar of character education in the digital era, and to identify strategies for strengthening it. The study employed a library research method using documentation techniques to collect data from books, policy documents, and national and international scholarly articles retrieved through Google Scholar, Publish or Perish, and journal databases. The data were analyzed using content analysis. A total of 25 articles that met the inclusion criteria were selected as the primary sources. The findings indicate that tolerance is the most practical indicator of religious moderation in shaping students' character within a pluralistic society. The digital era presents challenges such as opinion polarization, echo chambers, hate speech, and digital intolerance that may weaken tolerant attitudes. Strengthening tolerance can be achieved through curriculum integration, teachers' role modeling, habituation of tolerant behavior, enhancement of religious digital literacy, and collaboration among schools, families, and communities. This study contributes conceptually by synthesizing strategies for strengthening tolerance as a foundation for character education that is responsive to the challenges of the digital era. Theoretically and practically, these findings imply that religious moderation programs in schools should place tolerance at the center of curriculum design, teacher training, and digital literacy initiatives rather than treating it as a peripheral topic. This study is limited by its reliance on secondary literature obtained through a library research design, which does not involve direct empirical validation in the field, and by the restricted number and scope of the reviewed articles, so the findings should be interpreted as a conceptual synthesis rather than a generalizable empirical result.